Pelatihan Penggunaan KIT IPA dan Pengembangan LKPD Berbasis Praktikum untuk Guru IPA - Usmeldi Usmeldi; Risda Amini (Jurnal Abdimas Prakasa Dakara)
Practicum is the most important part of learning science because science is based on physical symptoms in everyday life. Each topic of science learning should be taught through practicum or demonstration conducted in the laboratory. In public schools, generally, there are many study groups, making it difficult for teachers to schedule practicum activities. Integrated Instrument Components (KIT) is one solution to the limitations of tools in the laboratory. The practicum KIT is a set of practicum tools that are packaged in such a way in a box containing practicum tools. The results of the initial survey at partner schools show that: (1) Teachers have difficulty using the science practicum KIT. (2) Laboratory and KIT for science practicum are available at school. (3) Teachers have difficulty in developing student worksheets (LKPD). (4) The use of science laboratories is still lacking because science teachers' areas of expertise are physics education and biology education. The purpose of the community partnership program (PKM) activity is to improve the ability of science teachers to use the practical KIT and develop practicum-based LKPD in accordance with the tools available in the science kit. The method of carrying out activities is the method of lecture, discussion, demonstration, and practice. The activity data collection instruments are in the form of questionnaires, observation sheets, and LKPD assessment sheets. The results of the PKM activity show that the skills of the trainees using the science practicum KIT are in a good category. The ability to develop LKPD is included in the good category. The resulting LKPD is in a good category.